CFD modeling of the ethylene–vinyl acetate copolymerization autoclave reactor: Effects of comonomer ratio on reactor dynamics and copolymer properties - Shin, Sunkyu; Lee, Damin; Oh, Ji Ye; Kim, Youngjo; Park, Myung June; Lee, Won Bo (Chemical Engineering Science, 2023)
Computational fluid dynamics (CFD) modeling of an industrial ethylene–vinyl acetate autoclave copolymerization reactor was conducted to evaluate the effects of comonomer ratios on reactor dynamics and product properties, including the molecular weight distribution (MWD), and copolymer composition. To accurately predict the MWD of copolymer chains under highly nonideal mixing conditions at a reduced computational cost, the CFD-multicompartment model and probability generating function (PGF) transform were applied. The effectiveness of the developed model was validated by the satisfactorily consistent plant data and simulated results. The model revealed that an increase in the vinyl acetate (VA) content significantly decreased the temperature, promoting combinational termination and chain transfer to polymer reaction for a broad copolymer MWD. The pseudo-kinetic-based analysis showed that VA was consumed more slowly than ethylene, resulting in its lower value in the copolymer composition than that of the comonomer ratios. However, despite nonideal mixing, the copolymer composition was maintained to be uniform for the copolymers produced over the entire reactor volume. In conclusion, the proposed model can be used to understand the governing behaviors of copolymerization under nonideal mixing conditions, design commercial copolymerization reactors, and predict copolymer product qualities.
Keywords: Autoclave reactors; Computational fluid dynamic-multicompartment; Copolymerisation; EVA copolymerization; Generating functions; Industrial autoclave; Industrial autoclave reactor; Kinetic rate constants; Molecular-weight distributions; Probability generating function; Pseudo-kinetic rate constant; Pseudo-kinetics; CFD-multicompartment; EVA copolymerization; Industrial autoclave reactor; Molecular weight distribution; Probability generating function; Pseudo-kinetic rate constants